Functional polymorphisms in cell death pathway genes FAS and FASL contribute to risk of lung cancer. Issue 6 (3rd June 2005) - Zhang, X; Miao, X; Sun, T; Tan, W; Qu, S; Xiong, P; Zhou, Y; Lin, D
Abstract : Background: The FAS and FASL system plays a key role in regulating apoptotic cell death and corruption of this signalling pathway has been shown to participate in immune escape and tumorigenesis. There is reduced expression of FAS but elevated expression of FASL in many types of human cancers including lung cancer. We recently reported an association between functional polymorphisms in FAS (−1377G→A) and FASL (−844T→C) and risk of oesophageal cancer. Objective: To examine the contribution of these polymorphisms to risk of developing lung cancer. Methods: Genotypes of 1000 lung cancer patients and 1270 controls were analysed by PCR based restriction fragment length polymorphism. Associations with risk of lung cancer were estimated by logistic regression. Results: Compared with non-carriers, there was a 1.6 fold excess risk of developing lung cancer for carriers of the FAS −1377AA genotype (odds ratio (OR) 1.59, 95% confidence interval (CI) 1.21 to 2.10; p = 0.001), and 1.8 fold excess risk (OR 1.79, 95% CI 1.26 to 2.52; p = 0.001) for carriers of FASL −844CC. Gene–gene interaction of FAS and FASL polymorphisms increased risk of lung cancer in a multiplicative manner (OR for the carriers of both FAS −1377AA and FASL −844CC genotypes 4.18, 95% CI 2.83 to 6.18). Gene–environment interaction of FAS or FASL polymorphism and smoking associated with increased risk of lung cancer was also found. Conclusion: These results are consistent with our initial findings in oesophageal cancer and further support the hypothesis that the FAS and FASL triggered apoptosis pathway plays an important role in human carcinogenesis.